ANALYSIS OF NITRITE CONTENT IN FRESH-CUT VEGETABLES UNDER DIFFERENT STORAGE CONDITIONS - Xing XU; Yanping LI; Fei YANG; Yan ZHANG; Ping SHU (Food and Environment Safety)
This study quantitatively assessed the nitrite content (calculated by sodium nitrite) in four commonly consumed fresh-cut vegetables using spectrophotometric analysis. The investigation focused on the variations in nitrite levels in tender ginger, old ginger, chili, and garlic under varying storage temperatures and durations. Results indicated that nitrite concentrations were higher in vegetables stored at ambient temperature compared to those stored at lower temperatures. Notably, the nitrite content in both tender and old ginger exhibited a rapid increase at ambient temperature, reaching approximately 160 mg/kg, significantly exceeding the safe consumption threshold for humans. Over time, nitrite levels initially rose and subsequently declined, whereas no substantial changes were observed in chili and garlic during storage. Furthermore, no significant difference was detected between the nitrite content and the baseline values in vegetable samples with intact tissue structures under identical storage conditions. In conclusion, this study provides a theoretical foundation for mitigating the risk associated with nitrite consumption in fresh-cut vegetables, thereby contributing to the protection of human health.